Psychosocial Impacts of Non-Fatal Firearm Injuries on Youth: Findings from a Qualitative Study - Annalyn S. DeMello PhD; Jeff R. Temple PhD; Liam de Vassal BSN; Irma Alvarado PhD; Angela Waguespack; Monique R. Pappadis PhD; Jong O. Lee MD; Leila G. Wood PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Most adolescents and young adult victims of firearm violence survive, yet the mental and behavioral health outcomes associated with these incidents remain understudied. Given the potential for recurrent violence victimization and long-term psychosocial sequela after being shot, understanding the experiences of firearm injury survivors is a critical area for development. We conducted a qualitative study to explore the development of attitudes, describe psychosocial consequences, and contextualize behavioral and social outcomes among young, gunshot wounded (GSW) patients from a Level 1 trauma center in southeast Texas. A retrospective chart review and prospective recruitment of GSW patients aged 15 to 29 years old was conducted between January 2019 and February 2023. A semi-structured, individual interview was conducted via Zoom with 11 participants (8 interpersonal assault survivors and 3 survivors of unintentional/accidental self-shootings). Most participants were shot 1 to 2 years prior to the interview. Themes included: (1) post-traumatic stress symptoms persisted, marked by flashbacks, paranoia, distrust, and anxiety. This led to sleep loss, marijuana use, and loss of enjoyment in activities; (2) loneliness and social isolation were directly related to the injuries and common among young adults who incurred body image alterations; and (3) fervor for firearm ownership, carriage, and gun use increased post-injury. Healthcare systems and the larger community have important roles to play in promoting mental healing and enhancing societal safety through research and practice.